2004
DOI: 10.1128/jvi.78.15.8245-8253.2004
|View full text |Cite
|
Sign up to set email alerts
|

p53 Targets Simian Virus 40 Large T Antigen for Acetylation by CBP

Abstract: Simian virus 40 (SV40) large T antigen (T Ag) interacts with the tumor suppressor p53 and the transcriptional coactivators CBP and p300. Binding of these cellular proteins in a ternary complex has been implicated in T Ag-mediated transformation. It has been suggested that the ability of CBP/p300 to modulate p53 function underlies p53's regulation of cell proliferation and tumorigenesis. In this study, we provide further evidence that CBP activity may be mediated through its synergistic action with p53. We demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 45 publications
3
57
0
Order By: Relevance
“…We tested our ability to reproduce these findings using the FLS platform technology. In CV-1 cells expressing p53/EGFP/ NS(471-721), consistent with the published results obtained by other methods (27), TAg(250 -627) was sufficient to associate (i.e. colocalize) with p53 in FLS (Fig.…”
Section: Bait/egfp/ns(471-721))supporting
confidence: 91%
See 2 more Smart Citations
“…We tested our ability to reproduce these findings using the FLS platform technology. In CV-1 cells expressing p53/EGFP/ NS(471-721), consistent with the published results obtained by other methods (27), TAg(250 -627) was sufficient to associate (i.e. colocalize) with p53 in FLS (Fig.…”
Section: Bait/egfp/ns(471-721))supporting
confidence: 91%
“…The smallest contiguous region of TAg shown to retain strong interaction with p53 comprises 377 centrally located amino acids (TAg(250 -627)) (27). Furthermore deletion of 11 amino acids within this region of full-length TAg (TAg(⌬434 -444)) has been shown to ablate the interaction with p53 (28).…”
Section: Bait/egfp/ns(471-721))mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of such screening, we identified several acetylated proteins including the SV40 large T antigen (T-Ag). Most recently, it was demonstrated that T-Ag could be acetylated by CBP (Poulin et al, 2004). However, the regulation of the T-Ag acetylation and its biological function remained obscure.…”
Section: Introductionmentioning
confidence: 99%
“…All studies used low passage C2C12 (passages 3-6). P300 Ϫ/Ϫ mouse embryonic fibroblasts (28) were cultured in DMEM supplemented with 10% FBS as described previously (29).…”
Section: Methodsmentioning
confidence: 99%